2013
DOI: 10.1111/jgs.12219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Stimulated Salivary Flow in Adults

Abstract: The literature on the effect of age on saliva production, which has implications for health, quality of life, differential diagnosis, and case management, remains inconclusive. Physiological changes, motor and sensory, are frequently reported with increasing age. It was hypothesized that there would be a change in saliva production with older age. Whole stimulated saliva was collected by asking participants to chew gauze for 1 minute and then comparing the weight of saliva produced according to age and sex. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 30 publications
1
42
0
1
Order By: Relevance
“…Our results show that unstimulated saliva flow rate was approximately 32% higher for male subjects ( p < .01; η 2 = 0.130) and decreased with age (subjects aging 71–80 years had approximately 52% lower flow rate than subjects aging 31–40 years) ( p < .01; η 2 = 0.262). Ben‐Aryeh et al () did not observed effects of gender and age (young adults: n = 39, average age: 37 years and elderly adults: n = 39, average age: 66 years) on the flow rates of whole and parotid saliva (both resting and stimulated), while Smith et al () reported a significant lower secretion of stimulated whole saliva in elderly adults ( n = 180, ≥70 years) in comparison to young ( n = 180, 20–30 years) and middle‐aged ( n = 180, 40–50 years) adults. No differences in saliva flow rate between young and middle‐aged adults nor between males and females were observed (Smith et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Our results show that unstimulated saliva flow rate was approximately 32% higher for male subjects ( p < .01; η 2 = 0.130) and decreased with age (subjects aging 71–80 years had approximately 52% lower flow rate than subjects aging 31–40 years) ( p < .01; η 2 = 0.262). Ben‐Aryeh et al () did not observed effects of gender and age (young adults: n = 39, average age: 37 years and elderly adults: n = 39, average age: 66 years) on the flow rates of whole and parotid saliva (both resting and stimulated), while Smith et al () reported a significant lower secretion of stimulated whole saliva in elderly adults ( n = 180, ≥70 years) in comparison to young ( n = 180, 20–30 years) and middle‐aged ( n = 180, 40–50 years) adults. No differences in saliva flow rate between young and middle‐aged adults nor between males and females were observed (Smith et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…78,79 Yeh et al 80 identified a reduction in the SFR of elderly, even those not using systemic drugs, suggesting a relation between salivary dysfunction and ageing. Smith et al 71 investigated whole stimulated saliva and demonstrated that healthy adults aged 70 and older had lower levels of salivary flows than younger adults (<50).…”
Section: Ageingmentioning
confidence: 98%
“…While some authors have demonstrated impaired glandular function, others have not found salivary dysfunctions in the healthy and non-users of drugs elderly. [71][72][73][74][75][76][77] According to Tylenda et al 74 , ageing leads to the loss of about 30% of acinar cells, with substitution of secretory components by fibrous and adipose tissue. Ghezzi and Ship 75 found that after the use of an anticolinergic drug, glandular function is more affected in the elderly than in young individuals.…”
Section: Ageingmentioning
confidence: 99%
“…Although association between salivary flow rate and age has been widely reported, 24 Smith et al, 25 however, reported no association. Likewise, the present study which showed reduction in salivary flow as the age increases also showed with logistic regression for sex and age that the net effects effect of age and sex in accounting for reduced salivary flow was found to be statistically insignificant.…”
Section: Discussionmentioning
confidence: 96%